Elevation of YKL-40 in the CSF of Anti-NMDAR Encephalitis Patients Is Associated With Poor Prognosis - Chen, Jinyu; Ding, Yuewen; Zheng, Dong; Wang, Zhanhang; Pan, Suyue; Ji, Teng; Shen, Hai-Ying; Wang, Honghao (Frontiers in Neurology, 2018)
Abstract Objective: Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis predominantly affects children and young women; the disease can have a multistage presentation and exhibit a wide variety of neuropsychiatric features. This study aimed to investigate the profile of YKL-40 (Chitinase 3-like 1) in anti-NMDAR encephalitis patients and evaluate its association with modified Rankin Scale (mRS) scores and expression of inflammatory cytokines. Methods: A total of 66 patients were enrolled in this study, 33 with anti-NMDAR encephalitis, 13 with viral meningitis and 20 with non-inflammatory neurological disease. Patients were evaluated to determine mRS scores at disease onset and at the 3-month follow-up; cerebrospinal fluid (CSF) samples were collected in the meantime. CSF levels of YKL-40 and cytokines (TNF-α, IL-6, IL-10) were measured by enzyme-linked immunosorbent assay. Results: CSF levels of YKL-40 and inflammatory cytokines (TNF-α, IL-6, IL-10) were all more highly elevated in patients with anti-NMDAR encephalitis at the acute stage of disease compared with the controls. Levels of CSF YKL-40 were correlated with levels of IL-6 both at disease onset and at the 3-month follow-up. Changes in YKL-40 levels were significantly correlated with improved mRS scores in patients with anti-NMDAR encephalitis. Conclusion: Our study suggests that CSF levels of YKL-40 in patients with anti-NMDAR encephalitis were increased and correlated with clinical mRS scores. This may be reflective of the underlying neuroinflammatory process. YKL-40 demonstrates potential as a possible biomarker for the prognosis of anti-NMDAR encephalitis.